Who decides? Resolving failed banks in a European framework - Christopher Gandrud; Mark Hallerberg (Bruegel, 2013)
As the basis for a European regime for resolving failing and failed banks, the European Commission has proposed the Bank Resolution and Recovery Directive (BRRD) and a regulation establishing a European Single Resolution Mechanism (SRM) and a Single Bank Resolution Fund (SBRF). There is a debate about which parts of the proposed SRM-SBRF to add to the BRRD. The BRRD sets out a resolution toolkit that can be used by national resolution authorities. The SRM would involve European institutions more at the expense of national resolution authorities. This change could affect resolution outcomes. Domestic resolution authorities might be more generous than supranational authorities in providing assistance to banks. A supranational approach might be more effective in minimising costs for taxpayers. But regardless of the final design, more attention is needed to ensure that resolution authorities are politically independent from governments. When public support is provided to failed institutions it should come from a bankfunded resolution fund. This would reduce taxpayers' direct costs, and would make banks less likely to take risks and advocate for bailouts.
Keywords: 330; Bankinsolvenz; Bankenkrise; EU-Bankrecht